Vestibular syndrome in giant anteater (Myrmecophaga tridactyla) - De Oliveira, Fabrício Singaretti; Carvalho, Paula Fernanda Gubulin; De Camargo, Mauro Henrique Bueno; Delfini, Aline; Martins, Leandro Luís [UNESP] (Universidade Estadual de Londrina, 2009)
The vestibular syndrome is a well-defined disease in domestic animals but little known in wild ones. Here this affection of central origin is described in a caquetic adult female giant anteater (Myrmecophaga tridactyla), which presented circling behavior, extensor hypermetry in thoracic limbs, head tilt and spontaneous horizontal and positional vertical nystagmus. The animal received tube feeding twice daily and dexamethasone was given subcutaneous once daily at the dosis of 6mg/kg, with a progressive improvement of health after the second day of treatment. Dose was reduced to a half from fourth to sixth day, and to a quarter on seventh day, when the animal died. On the fifth day, however, circle deambulation had ceased and hypermetry, head tilt and nystagmus were reduced. Treating vestibular syndrome is a challenge in wild animal practice. Treatment is affected by hyporexia and anorexia, making difficult the animals' health improvement, which generally present muscle atrophy.
Síndrome vestibular em tamanduá-bandeira (Myrmecophaga tridactyla)
Keywords: Giant anteater; Myrmecophaga tridactyla; Vestibular syndrome